Education on healthy living behavior during self-isolation for children based on the guidelines of Ikatan Dokter Anak Indonesia - Indriyati Hadi Sulistyaningrum; Arifin Santoso; Fildza Huwaina Fathnin (Universitas Muhammadiyah Magelang, 2023)
This community service activity aims to educate children less than 5 years old, as an effort to provide information related to the consumption of drugs, vitamins and healthy living behavior while doing self-isolation. The community service method used is to provide education related to the procedures for consuming drugs, vitamins, and healthy living behaviors that are associated with conditions when children undergo independent isolation. The guidelines used in the education process are the guidelines for child self-isolation published by Ikatan Dokter Anak Indonesia. This service was carried out at Raudhatul Adfal IT Cendekia Kebonagung, Demak, Central Java. The results obtained are an increase in understanding of students and parents in consuming vitamins, independent isolation, and healthy clean-living behavior.